Efektivitas Pengangkutan Tandan Buah Segar Menggunakan Gerobak Sorong dan Becak Angkut Tanaman Kelapa Sawit (Elaeis Guineensis Jacq) Di Divisi III Kebun Bekiun PT. Langkat Nusantara Kepong - Walmadri Walmadri; Alwi Andrean; Febriana Roosmawati; Fastabiqul Khairad (CULTIVATE: Journal of Agriculture Science, 2025)
The transportation of Fresh Fruit Bunches (FFB) aims to deliver FFB and loose fruits to the mill in good condition through careful handling and adherence to delivery schedules, ensuring optimal palm oil mill operations. Freshly harvested FFB must be transported immediately for prompt processing. This study evaluates the effectiveness of FFB transportation at PT. Langkat Nusantara Kepong, Bekiun Estate, Division III, located in Langkat Regency, North Sumatra Province. A descriptive analysis with a purposive sampling method was used, collecting primary and secondary data from reliable sources. The results show that cargo rickshaws are more efficient for transporting FFB from the collection point (pasar pikul) to the loading ramp (TPH), carrying an average of 15.3 FFB with an average bunch weight of 114.87 kg per trip within 05:17 minutes, while wheelbarrows transport an average of 14.6 FFB with an average bunch weight of 244.9 kg per trip within 05:31 minutes.